The Development of Participatory Tools in Central and Eastern Europe: A Solution for the Crisis of Representative Democracy? (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
This study aims to analyse participatory tools developed in Central and Eastern Europe, in order to understand their potential impact on strengthening citizen participation in the decision-making process, and in countering the widespread lack of trust in public authorities.
Keywords: Representative Democracy; Partecipatory Democracy; Crisis of Democracy; Participatory Tools; Central and Eastern Europe